ISIS : Inside the Army of Terror - Weiss, Michael; Hassan, Hassan (New York Regan Arts, 2016)
In ISIS: Inside the Army of Terror, Syrian journalist Hassan Hassan and American analyst Michael Weiss explain how the terrorists of ISIS evolved from a nearly defeated insurgent group into a jihadi army--armed with American military hardware and the capability to administer a functioning state. Weiss and Hassan, who have both been on the frontlines of the Syrian revolution, have interviewed dozens of experts, American military and intelligence officials, and ISIS fighters to paint the first comprehensive picture of the rise and expansion of America's most formidable terrorist enemy.
Include Notes and Index.
Keywords: Terrorism -- Terrorists -- Middle East -- Terrorism--Religious aspects--Islam